2022
DOI: 10.3390/electronics11121870
|View full text |Cite
|
Sign up to set email alerts
|

FPGA-Based Antipodal Chaotic Shift Keying Communication System

Abstract: The current work presents a novel digital chaotic communication system with antipodal chaotic shift keying modulation, implemented in a field-programmable gate array (FPGA). Such systems provide high security on the physical communication level and can be used in wireless sensor network systems. A modified Chua circuit chaos generator and error linear feedback chaotic synchronization are implemented in FPGA and used to develop a chaotic communication system with digital transmitter and receiver an analog in-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The hardware design of a chaotic system can be performed using the MATLAB tool known as Simulink, 17 but the designer cannot take control on the manipulation of bits, as done when using numerical methods to discretize the block description of a dynamical system 16 . The use of the chaotic systems implemented on FPGAs is quite important in applications as for the development of digital chaotic communication systems, as shown in Capligins et al, 17 where the authors claim the FPGA design of a modified Chua's circuit along an antipodal chaotic shift keying modulation provide high security on the physical communication level and can be used in wireless sensor network systems. On this regard, as a hyperchaotic system provides better chaotic behavior than Chua's circuit, several applications can be enhanced using our proposed FPGA design of the new 4‐D hyperchaotic two‐scroll system with hidden attractor.…”
Section: Fpga Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…The hardware design of a chaotic system can be performed using the MATLAB tool known as Simulink, 17 but the designer cannot take control on the manipulation of bits, as done when using numerical methods to discretize the block description of a dynamical system 16 . The use of the chaotic systems implemented on FPGAs is quite important in applications as for the development of digital chaotic communication systems, as shown in Capligins et al, 17 where the authors claim the FPGA design of a modified Chua's circuit along an antipodal chaotic shift keying modulation provide high security on the physical communication level and can be used in wireless sensor network systems. On this regard, as a hyperchaotic system provides better chaotic behavior than Chua's circuit, several applications can be enhanced using our proposed FPGA design of the new 4‐D hyperchaotic two‐scroll system with hidden attractor.…”
Section: Fpga Implementationmentioning
confidence: 99%
“…Recent works show the implementation of hyperchaotic systems using field‐programmable gate arrays (FPGA), as they have advantages for fast verification and prototyping, as already shown in previous works 16,17 . The hardware design in this case makes use of fixed‐point notation to perform computer arithmetic, and the length of the number of bits that are used to process the signals depends on the amplitudes of the state variables of the dynamical system.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…When the current is re-applied, the memristor exhibits this stored resistance value. In our computer simulators the behavior of memristors is described by a circuit emulator published in [17,51,52]. For more details on the emulator and the properties of memristor-based hyperchaotic systems it refer to [53,54].…”
Section: Memristor-based Chaotic Systemmentioning
confidence: 99%
“…By comparing the results with other modulation schemes using the bit error rate (BER) graph, the study demonstrated the potential of the proposed chaos-based system for secure communication. Capligins et al proposed a new digital chaotic communication system featuring antipodal chaotic shift keying modulation [51]. The system was implemented using a fieldprogrammable gate array (FPGA) and offers enhanced security at the physical communication level.…”
Section: Introductionmentioning
confidence: 99%